INGLIZ VA O‘ZBEK TILLARIDA OILA KONSEPTINING DIAXRON VA SINXRON TAHLILI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Studying the concept of family in English and Uzbek is an important field of research that studies the linguistic foundations and phenomena of personal terminology in both languages. The field of conceptology is complex and specialized vocabulary is very useful for effective communication in this field. Studying the concept of family in English and Uzbek takes the historical development of the family concept in both languages, the development of the family concept in both languages, and personal conceptology in both languages.
Keywords: family, individual, diachronic, synchronic, society.